Bicompartmental Bucket Handle Meniscal Tear with Chronic ACL Deficiency Causing a Rare Triple PCL and Triple Cruciate Sign: A Case Report. Issue 2 (April 2021) - Sales, Eric; Gupta, Sunny; Daines, Benjamin; Baker, Alexandra; Landgrabe, Melanie; Zeini, Ibrahim Mamdouh; Youmans, D. Harrison; Osbahr, Daryl Christopher
Abstract : Case: A 16-year-old football player presented with chronic ACL deficiency along with bicompartmental bucket handle meniscal tears. Conclusion: We present a "triple cruciate" sign in addition to the triple posterior cruciate ligament (PCL) sign seen on Magnetic Resonance Imaging (MRI) to aid in diagnosing this injury.